Governance and human resources for health - Dieleman Marjolein; Hilhorst Thea (BMC, 2011)
Abstract Despite an increase in efforts to address shortage and performance of Human Resources for Health (HRH), HRH problems continue to hamper quality service delivery. We believe that the influence of governance is undervalued in addressing the HRH crisis, both globally and at country level. This thematic series has aimed to expand the evidence base on the role of governance in addressing the HRH crisis. The six articles comprising the series present a range of experiences. The articles report on governance in relation to developing a joint vision, building adherence and strengthening accountability, and on governance with respect to planning, implementation, and monitoring. Other governance issues warrant attention as well, such as corruption and transparency in decision-making in HRH policies and strategies. Acknowledging and dealing with governance should be part and parcel of HRH planning and implementation. To date, few experiences have been shared on improving governance for HRH policy making and implementation, and many questions remain unanswered. There is an urgent need to document experiences and for mutual learning.